Investigation and assessment of dependences of the total carbon on pH in Neris regional park soil - Baltrėnas, Pranas; Pranskevičius, Mantas; Lietuvninkas, Arvydas (Journal of Environmental Engineering and Landscape Management, 2010)
Soil is one of the most important natural subsystems of the Earth’s landscapes, which is exceptionally vital for a human being as the main source of food resources. In order to take care of the future one of the most relevant problems of the mankind is to preserve soils of the Earth, their fertility and normal state under conditions of the increasing technogenic effect and degradation of natural landscapes. As the global warming has already started, its after‐effects, which will be invertable faced by the Lithuanian agriculture, must be overcome as an additional negative factor. The paper aims at revealing the dependence of the total carbon on pH. It also focuses on the impact of climate change on the total carbon and soil degradation. Article in English. Bendrosios anglies priklausomumo nuo pH Neries regioninio parko dirvožemyje tyrimas ir vertinimas Santrauka. Dirvožemis yra vienas iš svarbiausių gamtinių Žemės landšaftų posistemių, išimtinai svarbus žmogui kaip pagrindinis maisto išteklių šaltinis. Rūpinantis ateitimi, viena iš aktualiausių žmonijos problemų – išsaugoti Žemės dirvožemius, jų derlingumą ir normalią būklę vis didejančio technogeninio poveikio ir gamtinių landšaftų degradacijos sąlygomis. Kaip papildomą neigiamą faktorių privalu įveikti prasidėjusio globalaus atšilimo pasekmes, su kuriomis neišvengiamai susidurs ir Lietuvos žemės ūkis. Straipsnyje siekiama atskleisti bendrosios anglies priklausomybę nuo pH, atkreipti dėmesį į klimato kaitos itaką dirvožemio degradacijai. Reikšminiai žodžiai: dirvožemis, bendroji anglis, pH, dirvožemio tyrimai. Исследование и анализ общего углерода и его зависимости от pH в региональном парке «Нерис» Резюме. Почва является одной из важнейших подсистем природных ландшафтов Земли, имеющей особенно важное значение для людей в качестве основного источника пищи. Одной из наиболее неотложных задач, стоящих перед человечеством, обеспокоенным своим будущим, является сохранение почв Земли, их плодородия и здорового состояния в условиях усиливающегося техногенного воздействия и деградации природного ландшафта. При этом придется преодолеть и уже начавшееся глобальное потепление, которое неизбежно коснется литовского сельского хозяйства. В статье предпринята попытка выявить зависимость общего углерода от рН, а также обратить внимание на последствия, наносимые изменением климата общему углероду, а также на деградацию почв. Kлючевые слова: почва, общий углерод, рН, исследование почв. First Publish Online: 10 Feb 2011